PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN FIRST MEDIA DI KOTA TEGAL - Muhammad David Bagus Rahendra; Audita Nuvriasari (Jurnal Ekonomi Dan Bisnis, 2022)
This study aims to analyze the influence of service quality, price perceptions, and promotions on the purchasing decisions of First Media consumers in Tegal City. In this study the authors used a sample of ninety six respondents. These respondents are First Media consumers in Tegal City with several criteria that have been determined by the author. The sampling technique uses a nonprobability sampling technique . The type of data in this study is quantitative data, the data sources used are primary and secondary data. The data analysis used in this research is a multiple linear regression test. The results of the hypothesis test prove that service quality has no significant effect on First Media's consumer purchasing decisions. This shows that service quality is not a variable that can influence purchasing decisions. While the perception of price and promotion positive and significant effect on purchasing decisions. This shows that the higher the perception of price and promotions carried out by First Media, the more it will encourage an increase in purchasing decisions made by consumers. The results of the determination test show that service quality, price perception, and promotion simultaneously able to influence the purchase decision of 52.7 % . while the remaining 47.3% is influenced by other factors outside the variables of this study. Keywords: Service Quality, Perceived Price, Promotion, Purchase Decision